Multi-physics continuum modelling approaches for metal powder additive manufacturing: a review - Alba-Baena, Noé (2020)
This paper aims to present a systematic approach in the literature survey related to metal additive manufacturing (AM) processes and its multi-physics continuum modelling approach for its better understanding. Design/methodology/approach